2019
DOI: 10.1002/srin.201900212
|View full text |Cite
|
Sign up to set email alerts
|

Strain Partitioning and Softening Mechanisms of δ/γ in Lean Duplex Stainless Steels during Hot Deformation

Abstract: A novel lean duplex stainless steel (DSS) with excellent hot workability is successfully developed, referred as 21Cr‐DSS. The strain partitioning and softening mechanisms of the constituent phases in the novel steel are elucidated and compared with the conventional DSS. The strain is preferentially accommodated in the soft ferrite phase, leading to the significant strain localization and a faster restoration of dynamic recovery and dynamic recrystallization (DRV or DRX) in ferrite, whereas conventional DSS is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…[ 9 ] The chemical compositions of δ, γ, σ, and γ 2 phases were analyzed by SEM–EDS, as shown in Figure 3b–d, which is consistent with the result from the studies. [ 9–13 ] Cr and Mo were rich in ferrite, whereas Ni mainly partitioned in austenite. The Mo and Cr contents in σ phase were higher than those in δ phase and γ phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] The chemical compositions of δ, γ, σ, and γ 2 phases were analyzed by SEM–EDS, as shown in Figure 3b–d, which is consistent with the result from the studies. [ 9–13 ] Cr and Mo were rich in ferrite, whereas Ni mainly partitioned in austenite. The Mo and Cr contents in σ phase were higher than those in δ phase and γ phase.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Generally, Cr and Mo are enriched in ferrite, whereas Ni and N are austenite-stabilizing elements. [9][10][11][12][13] According to the pitting resistance equivalent (PRE ¼Cr þ 3.3% Mo þ 16% N), [4,6,9,[16][17][18] the partitioning of the alloying elements results in the difference of corrosion resistance of each phase. In addition, several works [4,9,10] indicated that partitioning of alloying elements in each phase was affected by annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, this equation is only applied considering the percentages of each of phase present as a function of the temperature, strain rate, and chemical composition of the alloy, therefore it does not consider the strain and stress distribution between phases 39,40 . In the future, it is possible to compare these results considering the effects of this phenomenon for this kind of steel.…”
Section: Generic Model For Fe-c-mn-si Alloys In the Intercritical Zon...mentioning
confidence: 99%
“…Even at the end of the forming process, the strain distribution shows higher strains in ferrite than in austenite [7]. Due to the high strain accumulation in ferrite, a faster softening behavior of ferrite can be observed [8].…”
Section: Introductionmentioning
confidence: 99%
“…This rule of mixture was validated for cold forming of a 1.4507 (AISI F255) super duplex steel by Cho et al [9] using measurements of micro-strains in ferrite and austenite and calculated stress-strain curves of ferrite and austenite single phase based on Ashby's one-parameter theory. For hot deformation, the rule of mixture was used by Zhao et al [8] to estimate the stress-strain partitioning coefficient at a total strain of 0.25, which indicates the degree of stress transfer from soft ferrite to hard austenite. The partitioning coefficient increases with the deformation temperature, which means that strain at high temperatures is more homogenously distributed between both phases.…”
Section: Introductionmentioning
confidence: 99%